Improving Water Efficiency in Solar Pumping Irrigation Systems: Case studies from Tunisia and Morocco - Lahham, Nisreen (2019)
As part of the seminar held by the International Food Policy Research Institute (IFPRI) in collaboration with IWMI, World fish and ICARDA “Options for improving irrigation water efficiency for sustainable agricultural development”.